HISTORY AND RESULTS OF THE INTRODUCTION OF PALMS (ARECACEAE C.H. SCHULTZ) ON THE SOUTHERN COAST OF THE CRIMEA - A. P. Maksimov; Yu. V. Plugata; V. P. Koba; A. F. Khromov (Труды по прикладной ботанике, генетике и селекции)
The results of the introduction of palms have been summarized, and the assortment, opportunities and conditions of their cultivation on  the Southern Coast of the Crimea (SCC) defined. Long-term  observations on the experimental plants with an assessment of their  prospects according to a frosting scale during severe winters and  biometric measurements of their habit by instrumental methods  have been conducted. The article describes the history and results of the palms' introduction beginning from 1814 up to the present  moment. It was established that growth and development of palms  in the NBG's arboretum depend not only on their winter resistance  but also on the growing conditions and cultivation practices. The  results of the palms' introduction over a 30-year span of the  research (1984-2014) through the example of their growth and  development in the NBG's arboretum have been summed up. The  data about the characteristic habits and reproductive capabilities for  the year 1984 have been provided and compared with the same  parameters obtained in 2014 on the same experimental trees. A  picture of actual damages of various palm species during severe  winters has been shown, and the degree of their tolerance to  extreme negative temperatures determined. A promising assortment of palms tested in the NBG's arboretum has been identified, and the  conditions of their cultivation on the SCC shown. The environmental  and biological criteria influencing growth and development of 12  species of palms have been defined. Recommendations as to  agricultural practices, protection in winter, and rational utilization of palms in ornamental gardening have been provided.